Ectopic tubal pregnancy with partial mole: a rare case - Patil, Nanda; Nazeer, Robina Mohamed; Tele, Jyoti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Hydatidiform moles are abnormal gestations characterised by the presence of hydropic changes in the placental villi associated with circumferential trophoblastic proliferation. They arise due to abnormal fertilization. Molar gestation commonly develops within the uterus but presence of molar changes in ectopic pregnancy is extremely rare. Author present a rare case of ectopic molar pregnancy in fallopian tube in a 20 years old female patient to highlight its clinicopathological features. Ectopic molar pregnancy in a fallopian tube is very rare and histopathological study is the gold standard for the exact diagnosis and further management.